PerfectBASH: Band‐selective homonuclear decoupling in peptides and peptidomimetics. (8th July 2018) - Ilgen, Julian; Kaltschnee, Lukas; Thiele, Christina M.
Abstract : Band selective techniques offer the highest sensitivity of all pure shift approaches and thus are the best choice for decoupling well‐separated 1 H‐frequency regions, such as the amide‐ or the α‐proton region of α‐peptides. They are inept to fully decouple the amide‐ and the α‐proton region simultaneously, though. Herein, we present a new homonuclear decoupling technique, which extends the capabilities of band selective decoupling using the perfect echo principle. This modification allows a complete backbone decoupling (amide‐ and α‐protons) in peptides and opens band selective homonuclear decoupling to substances with two mutually coupled protons in the spectral range of interest.